The Review on Impacts of Invasive Plants on The Physico-Chemical Characteristic of Water Body Quality - Mohd Zahari, Ahmad Fathanah; seswoya, Roslinda (Recent Trends in Civil Engineering and Built Environment, 2021)
Invasive aquatic plants may lead to local loss of diversity across the globe and also to deterioration in water quality. The major contribution of spreading of invasive aquatic plant are their sexual reproduction and dispersal mechanisms. regarding to that matter, the management should be following three phase which are prevention, early detection and fundamental knowledge about invasive aquatic plant behaviour. the management of invasive aquatic plan are important which enable us to sustain our water quality resources from being contaminate and polluted by the invasion of the invasive aquatic plant. This review provided useful information for the management on removal and control the spreading of invasive aquatic plant which also an effort to decrease the negative impacts on environment. This review is prepared to summarize 1) to categories the type of invasive aquatic plant., 2) to identify the factors for invasive aquatic plant growth, 3) to explain the impacts of invasive aquatic plants towards water quality, ecosystem and community., 4) to relate the water characteristic with the presence of invasive aquatic plant, 5) to categorize the method for invasive aquatic plant removal, and 6) to differentiate the control methods to maintain water body ecosystem. This review can be a significant reference for understanding the invasive aquatic plants.